Biochar and Humic Substances Roles for Nitrogen Transformation in Agriculture - Gagad Restu Pratiwi; Arinal Haq Izzawati Nurrahma (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Sustainable soil fertility management is crucial for global food security and addressing environmental challenges from modern agriculture. Soil health, alongside water availability, is essential for crop productivity, and soil degradation threatens food security by lowering yields and intensifying climate change. Nitrogen (N) cycling is central to soil fertility, supporting plant growth through nutrient replenishment and microbial activity. However, N is often lost through leaching, volatilization, and denitrification, reducing nitrogen use efficiency (NUE) and contributing to water pollution and greenhouse gas (GHG) emissions. Optimizing nitrogen retention in soils is vital for improving productivity and minimizing environmental harm. Biochar (BC) and humic substances (HSs) have emerged as effective strategies for improving N management. BC enhances soil fertility by increasing soil pH, cation exchange capacity, and water retention, while reducing nutrient leaching and promoting carbon sequestration. HSs, including humic acids (HA), fulvic acids (FA) and humin (HU), improve nutrient cycling by stimulating microbial activity and enhancing nutrient transport. Together, BC and HSs provide synergistic benefits for soil health, particularly in challenging environments like saline or nutrient-depleted soils. This review highlights the roles of BC and HSs in enhancing soil fertility, promoting N mineralization, and improving crop productivity. It emphasizes their potential for sustainable agricultural practices, climate change mitigation, and long-term soil health. Keywords: Biochar, Climate changes, Humic substances, Remediation, Soil fertility.